Evaluation of preemptive pregabalin efficacy on block characteristics and postoperative analgesia in patients undergoing infra-umbilical surgeries under spinal anesthesia: A prospective randomized double-blind placebo controlled study - Indira Kumari; Swati Dhania; Surendra Kumar Sethi; Santosh Choudhary; Ipra Jain; Vidhu Yadav (The Indian Anaesthetists' Forum)
Background and Aims: Spinal anesthesia is the most common technique used for infraumbilical surgeries. Preemptive analgesics have been reported to improve the quality of spinal anesthesia and enhance postoperative analgesia. The present study aimed to evaluate the efficacy of preemptive oral pregabalin on the quality of spinal anesthesia and postoperative analgesia in patients undergoing infraumbilical surgeries. Materials and Methods: Seventy patients American Society of Anesthesiologists physical status I and II, posted for infra-umbilical surgeries under spinal anesthesia, were randomly allocated into two groups. Group P (n = 35) received preemptive oral pregabalin 150 mg and Group C (n = 35) received placebo, 1 h before surgery. Duration of sensory block was the primary objective while onset of sensory and motor block, duration of motor block and analgesia, rescue analgesic consumption, and side effects were secondary objectives. Qualitative and quantitative variables were analyzed using Chi-square test and Student’s t-test, respectively. P < 0.05 was considered significant. Results: The duration of sensory block was significantly longer in Group P (156.71 ± 5.41 min) than in Group C (135.14 ± 7.22 min) (P = 0.001) (95% CI = 21.57 [18.53–24.61]). The duration of postoperative analgesia was significantly longer in Group P (529.71 ± 6.17 min) than in Group C (219.85 ± 5.21 min) (P = 0.001) (95% CI = 309.86 [307.14–312.58]). The duration of the motor block was also significantly longer in Group P (220.28 ± 4.19 min) than in Group C (195.71 ± 5.95 min) (P = 0.001) (95% CI = 24.57 [22.12–27.03]). Onset of sensory and motor block was comparable between both groups. The rescue analgesic consumption was also significantly lesser in Group P (P < 0.000). Sedation scores were higher in the pregabalin group with stable hemodynamics and minimal side effects. Conclusion: Pregabalin can be effectively used as preemptive analgesic as it improves the spinal block characteristics and enhances the duration of postoperative analgesia along with minimal side effects.